Endocarditis in a Prosthetic Aortic Valve: A Case Report and Literature Review - Romina Maria Rösch MD; Katja Buschmann MD; Lena Brendel MD; Thomas Schwanz MD; Christian-Friedrich Vahl MD, PhD (SAGE Publishing, 2019)
Background. Lactococcus garvieae (LG) is a gram-positive coccus known to be a major pathogen in aqua farming, which is responsible for severe outbreaks. Its incidence in humans is extremely rare. Prior to 1985, all bacteria in the genus Lactococcus were included in the Streptococcus genus. The first human infection was documented in 1991, and since then, the relevance and clinical significance in humans has increased. Case Description. We present the clinical course of an LG endocarditis in a 78-year-old man who had a history of exertional dyspnea. The patient's blood tests showed increased inflammation values, and a transesophageal ultrasound (TEE) showed a stenosis of the prosthetic aortic valve. Blood cultures were positive for LG, leading to a diagnosis of infective endocarditis. After 6 weeks of intravenous antibiotics and a prosthetic aortic valve replacement, the patient made a good recovery. Review of the Literature. After the first documented case in 1991 to 2018, 25 cases of LG endocarditis have been described in PubMed and MEDLINE. We reviewed all reported cases of LG endocarditis, commenting on predisposing risk factors, the course and outcome of the disease. Conclusion. LG endocarditis is a rare disease. Consumption of raw fish, abnormalities of the digestive tract, immune deficiency, and underlying cardiac conditions appear to be risk factors for an infective endocarditis due to LG. Improved determination techniques are likely to lead to a better and faster identification of the bacterium. This identification allows a faster and individualized therapy, which in turn affects the outcome.